Bronze Age and Iron Age archaeology at Thainstone Business Park, Inverurie, Aberdeenshire: an investigation of structures and funerary practices (Scottish Historical and Archaeological Internet Reports, 2021)
Headland Archaeology (UK) Ltd was commissioned by Axiom Project Services to undertake an archaeological excavation in advance of a commercial development at Thainstone Business Park, Aberdeenshire (NGR: NJ 7707 1809). Excavation identified the remains of a Middle Bronze Age roundhouse and a contemporary urned cremation cemetery. Evidence of Late Bronze Age cremation practices was also identified. A large roundhouse and souterrain dominated the site in the 1st or 2nd century AD. Material culture associated with the Iron Age structures suggested a degree of status to the occupation there.